2021
DOI: 10.1016/j.fct.2021.112087
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, immunity and potential target therapy of SARS-COV-2: A total scale analysis review

Abstract: Coronavirus disease-19 (COVID-19) is a complex disease that causes illness ranging from mild to severe respiratory problems. It is caused by a novel coronavirus SARS-CoV-2 (Severe acute respiratory syndrome coronavirus-2) that is an enveloped positive-sense single-stranded RNA (+ssRNA) virus belongs to coronavirus CoV family. It has a fast-spreading potential worldwide, which leads to high mortality regardless of lows death rates. Now some vaccines or a specific drug are approved but not available for every co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 287 publications
0
22
0
7
Order By: Relevance
“…In contrast, Calu-3 and Caco-2 endogenously express TMPRSS2 29 , which activates SARS-CoV-2 spike protein on cell surface so virus gets into these cell lines through direct cell membrane fusion. Cathepsin L inhibitor E-64d and TMPRSS2 inhibitor camostat mesylate were included as controls 30 . Our results showed that brilacidin inhibited SARS-CoV-2 pseudovirus entry into all cell lines tested with IC 50 values ranging from 12.0 ± 1.7 to 23.0 ± 1.6 µM (Figure 1).…”
Section: Brilacidin Inhibits Sars-cov-2 Pseudovirus Entry In Multiple Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, Calu-3 and Caco-2 endogenously express TMPRSS2 29 , which activates SARS-CoV-2 spike protein on cell surface so virus gets into these cell lines through direct cell membrane fusion. Cathepsin L inhibitor E-64d and TMPRSS2 inhibitor camostat mesylate were included as controls 30 . Our results showed that brilacidin inhibited SARS-CoV-2 pseudovirus entry into all cell lines tested with IC 50 values ranging from 12.0 ± 1.7 to 23.0 ± 1.6 µM (Figure 1).…”
Section: Brilacidin Inhibits Sars-cov-2 Pseudovirus Entry In Multiple Cell Linesmentioning
confidence: 99%
“…The antiviral activity of brilacidin was tested against HCoV-229E, HCoV-NL63 and HCoV-OC43 in Viral yield reduction (VYR) assays as previously described 30,[40][41][42] .…”
Section: Antiviral Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID-19 epidemic has seriously affected people's health, economic development, and social progress all over the world [ 5 ]. Although some COVID-19 vaccines have been approved, they are not available in all countries infected with SARS-CoV-2 [ 6 ]. With the persevering efforts of researchers, several options have been envisaged to control the emerging infections of COVID-19, such as monoclonal antibodies, peptides, oligonucleotide-based therapies, interferon therapies and small molecule drugs.…”
Section: Introductionmentioning
confidence: 99%